Abrus precatorius Leaf Extract Reverses Alloxan/Nicotinamide-Induced Diabetes Mellitus in Rats through Hormonal (Insulin, GLP-1, and Glucagon) and Enzymatic (α-Amylase/α-Glucosidase) Modulation. (24th July 2021) - Boye, Alex; Barku, Victor Yao Atsu; Acheampong, Desmond Omane; Ofori, Eric Gyamerah
Abstract : Background . Abrus precatorius is used in folk medicine across Afro-Asian regions of the world. Earlier, glucose lowering and pancreato-protective effects of Abrus precatorius leaf extract (APLE) was confirmed experimentally in STZ/nicotinamide-induced diabetic rats; however, the underlying mechanism of antidiabetic effect and pancreato-protection remained unknown. Objective . This study elucidated antidiabetic mechanisms and pancreato-protective effects of APLE in diabetic rats. Materials and Methods . APLE was prepared by ethanol/Soxhlet extraction method. Total phenols and flavonoids were quantified calorimetrically after initial phytochemical screening. Diabetes mellitus (DM) was established in adult Sprague-Dawley rats (weighing 120–180 g) of both sexes by daily sequential injection of nicotinamide (48 mg/kg; ip ) and Alloxan (120 mg/kg; ip ) over a period of 7 days. Except control rats which had fasting blood glucose (FBG) of 4.60 mmol/L, rats having stable FBG (16–21 mmol/L) 7 days post-nicotinamide/Alloxan injection were considered diabetic and were randomly reassigned to one of the following groups (model, APLE (100, 200, and 400 mg/kg, respectively; po ) and metformin (300 mg/kg; po )) and treated daily for 18 days. Bodyweight and FBG were measured every 72 hours for 18 days. On day 18, rats were sacrificed under deep anesthesia; organs (kidney, liver, pancreas, and spleen) were isolated and weighed. Blood was collected for estimation of serum insulin, glucagon, and GLP-1 using a rat-specific ELISA kit. The pancreas was processed, sectioned, and H&E-stained for histological examination. Effect of APLE on enzymatic activity of alpha ( α )-amylase and α -glucosidase was assessed. Antioxidant and free radical scavenging properties of APLE were assessed using standard methods. Results . APLE dose-dependently decreased the initial FBG by 68.67%, 31.07%, and 4.39% compared to model (4.34%) and metformin (43.63%). APLE (100 mg/kg) treatment restored weight loss relative to model. APLE increased serum insulin and GLP-1 but decreased serum glucagon relative to model. APLE increased both the number and median crosssectional area (×10 6 μ m 2 ) of pancreatic islets compared to that of model. APLE produced concentration-dependent inhibition of α -amylase and α -glucosidase relative to acarbose. APLE concentration dependently scavenged DPPH and nitric oxide (NO) radicals and demonstrated increased ferric reducing antioxidant capacity (FRAC) relative to standards. Conclusion . Antidiabetic effect of APLE is mediated through modulation of insulin and GLP-1 inversely with glucagon, noncompetitive inhibition of α -amylase and α -glucosidase, free radical scavenging, and recovery of damaged/necro-apoptosized pancreatic β -cells.